Research on a Training Model to Enhance the Enterprise Innovation and Practice Ability of Computer Science Students in Colleges and Universities - Zhang, Yingying (Journal of Educational Research and Policies, 2025)
This paper looks at how to better prepare computer science students for real-world innovation challenges. We surveyed 126 tech companies and found three main problems with current university programs: (1) course content isn’t keeping up with new technologies, (2) students don’t get enough hands-on experience, and (3) grading focuses too much on tests rather than practical skills. To fix this, we created a new teaching approach that combines: Up-to-date courses that change as technology advances. More opportunities to work on real company projects. Better ways to track student progress using digital portfolios; After testing this approach, we saw great results: 41% more students developed strong technical skills; Companies were 37% happier with graduates’ abilities; Student startup projects increased by 63%.